IMPLEMENTASI METODE PIECES TERHADAP KEPUASAN DAN KEPENTINGAN PENGGUNAAN APLIKASI CEISA MOBILE STUDI KASUS DIREKTORAT JENDERAL BEA DAN CUKAI - Veri Arinal; Nova Esterina Silitonga (CKI ON SPOT, 2021)
CEISA Mobile Application System is an application system used to assist service users incarrying out customs and excise activities and also helps improve the services of the DirectorateGeneral of Customs and Excise by utilizing current technological developments. This study aimsto analyze the factors that influence the successful implementation of the system and measure howsuccessful the application of the CEISA Mobile Application System is in the Directorate Generalof Customs and Excise Environment using the PIECES Framework method. The PIECESFramework method measures the success of an application system from the variables ofperformance, information and data, economy, control and security, efficiency, and security whichare related to the level of satisfaction and importance of the use of the application system. Theresearch method used is by distributing questionnaires through Google Forms links to users ofthe CEISA Mobile application system in the Directorate General of Customs and ExciseEnvironment. Data was obtained from 98 service users spread throughout Indonesia and thenprocessed using IBM SPSS Statistics 25 tools.